OPTIMALISASI PENDIDIKAN HUMANISTIK DI SEKOLAH DASAR: Studi Multisitus di SD Insan Mulia Surabaya dan SDS Wahidiyah Tulungagung - Rohman, Khabibur (LP2M IAIN Tulungagung, 2016)
The broke of the sense of humanity, scraped of religious values, the lost of identity of a nation that is one of them the background. The institutions of education that can hopefully deport the distortion of humanity values, preciselyless of implicate maximally reviews their task. In this era, the educations take care of cognitive aspect too, and less to take care of other external potentials.The Educations become less of meaningful, because it just is formalistic and only as transfer of knowledge. In this case, we need a humanistic education, that is a concept of education that help the students found reviews their skills, improve and the next they can actualize. Humanistic education could hopefully some individuals that have formed pure of humanitarian commitment, it means that human have awareness, freedom, and responsibility also as an individual and social also.Keywords: Optimization, Humanists, Elementary School